Política Nacional de Plantas Medicinais e Fitoterápicos no SUS e sua implementação por meio das farmácias vivas - Gondim, Jacqueline Marques da Silva (2021)
Medicinal plants have been used for millennia, being used in search of the cure of various diseases, being part of the culture of peoples, and even of religious rituals. In Brazil, its use has been validated by public policies, which aim to regulate its safe access. In this context, to guarantee the access, production and rational use of medicinal plants and herbal medicines, the Vivas Pharmacies project was created. The aim of this study was to analyze the implementation of the National Policy on Medicinal Plants and Herbal Medicines in the SUS through the implementation of Living Pharmacies. The methodology consists of a documentary and bibliographic research, of a descriptive character, developed from databases on internet sites to extract the material of interest. Data collection took place between March 2020 and October 2020, performing a search for journal articles, books, survey of official normative documents, in databases such as Portal de Periódicos Capes/MEC, PubMed, Scielo, Google Academic, Ministry of Health portal, Official Gazette of the Union, official website of state and municipal health secretariats, Anvisa and IBGE. For a survey of actions, public and regulatory policies in the scope of medicinal and herbal plants, normative and technical materials between 1982 and 2009 were sought. The period from 1983 to 2020 was considered to analyze how the institutionalization of Pharmacies took place. Cheers. In relation to public resources made available through public notices, ordinances and public calls, the period from 2012 to 2020 was considered; and for sociodemographic data, the period from 2012 to 2020 was retrieved, in which MS publications provided resources within the scope of the PNPMF. As a result, it is observed that actions, public and regulatory policies, contributed to the expansion of medicinal plants and phytotherapy programs in Brazil, as well as to the consolidation of the Live Pharmacy Program within the scope of the SUS. The financial resources were made available with regularity and specific destination, but distributed unevenly, considering the regional sociodemographic needs. Greater financial support would be needed for regions with greater socio-economic vulnerability, reducing bureaucracy in accessing resources, and strengthening regional public policies.